Parental Strategies in the Utilization of Traditional Games to Stimulate Early Childhood Growth and Development - Tatminingsih, Sri; Dewi , Anita Chandra; Sa’diyah, Rika; Satriana, Malpalni (JURNAL PENDIDIKAN USIA DINI, 2025)
Parents who are having children at a young age at this time tend to be those belonging to Gen Y and Gen Z. It's assumed that this generation belongs to the technologically literate generation. In reality, however, many parents still believe and apply beliefs or myths considered local wisdom in raising their children. Even though they belong to a sophisticated generation and are technology users, many of them still use the beliefs of previous generations in raising their children. One of these beliefs is traditional games. This research aims to investigate how millennial parents stimulate their children's growth and development through the use of local wisdom, especially traditional games. The research sample consisted of 150 millennial parents in the area of Jakarta - Bogor – South Tangerang – Tangerang City - Bekasi (Jabodetabek), Indonesia. This research uses a survey method. The 6-question questionnaire was distributed through G-form platform. The data was analysed qualitatively through grouping on the basis of similarity of responses and simple quantification with percentages. The research findings indicate that: 1) there are still parents who use local wisdom, especially traditional games, as a strategy to stimulate some of their children's growth and development; 2) the local wisdom that is applied is mostly the experience of their parents; 3) the strategy implemented through trial is flexible; 4) each parent has different strategies for the same local wisdom; 5) the main obstacle is the interference of other family members in the application of local wisdom to children. The implication of using local wisdom, especially traditional games, is that parents and other family members need to cooperate and agree when using traditional games to stimulate early childhood development